A comprehensive overview of the climatological composition of the Asian summer monsoon anticyclone based on 10 years of Aura Microwave Limb Sounder measurements. Issue 10 (17th May 2017) - Santee, M. L.; Manney, G. L.; Livesey, N. J.; Schwartz, M. J.; Neu, J. L.; Read, W. G.
Abstract: Intense deep convection associated with the Asian summer monsoon (ASM) lofts surface pollutants to the upper troposphere/lower stratosphere (UTLS), where strong winds and long chemical lifetimes allow intercontinental transport, affecting atmospheric composition around the globe. The Aura Microwave Limb Sounder (MLS), launched in 2004, makes simultaneous colocated measurements of trace gases and cloud ice water content (a proxy for deep convection) in the UTLS on a daily basis. Here we exploit the dense spatial and temporal coverage, long‐term data record, extensive measurement suite, and insensitivity to aerosol and most clouds of Aura MLS to characterize the climatological (2005–2014) composition of the ASM anticyclone throughout its annual life cycle. We use version 4 MLS data to quantify spatial and temporal variations in both tropospheric (H2 O, CO, CH3 Cl, CH3 CN, CH3 OH) and stratospheric (O3, HNO3, HCl) tracers on four potential temperature surfaces (350–410 K). Inside the mature anticyclone, all species exhibit substantial changes, not only from their premonsoon distributions in the ASM region but also from their summertime distributions in the rest of the hemisphere. Different tracers exhibit dissimilar seasonal evolution, and the exact location and timing of their extreme values vary. Although individual aspects of the anticyclone have been described previously, we present a uniquely comprehensive overview of the climatological seasonal evolution of the ASM and its impact on UTLS composition. This work provides valuable context for planned in situ measurements as well as a benchmark for model evaluation and future investigations of interannual variability and long‐term changes in monsoon processes. Key Points: Aura MLS v4 data are used to characterize the climatological composition and seasonal evolution of the Asian summer monsoon anticyclone Convective lofting of surface air enhances abundances of tropospheric but reduces abundances of stratospheric tracers in the anticyclone Different tracers exhibit dissimilar seasonal evolution, and the exact location and timing of extreme values vary from species to species